Laser treatment impact on the fabric 07C11-KV surface and its coating with zirconium - A. G. Anisovich; I. P. Akula; A. P. Laskovnev; V. I. Zhuravleva; M. I. Markevich; N. M. Chekan (Литьë и металлургия)
The results of laser radiation interaction with woven fabrics and coatings on them can be used as a basis for new technological processes. The morphology of the surface of a pure mixed fabric 07C11-KV (Mogotex) is studied and this fabric with a zirconium coating after laser exposure in the dual pulse mode. The modes under which tissue destruction occurs as a result of melting of the material under the action of a concentrated stream of laser radiation are established. It is shown that laser exposure in the twopulse mode in the energy range from 10 to 20J leads to complete material destruction with fabric edges melting.